Call metadata from: Data collection smart and simple: Evaluation and metanalysis of call data from studies applying the 5Q approach. - Eitzinger, Anton (2021)
The original research publication that uses the dataset evaluated the application of the 5Q approach (5Q) combined with interactive voice response (IVR) call campaigns for agile data collection. The dataset includes 37’503 call metadata from 102 IVR call campaigns and among five countries. The dataset provides insights to call status, average call duration, reached IVR blocks, and differences in response rate between different call types and survey topics.